Biostabilization of sediments by microbial mats in a temperate siliciclastic tidal flat, Bahia Blanca estuary (Argentina) - Cuadrado, Diana Graciela (2011)
Extensive microbial mats have been found in the siliciclastic tidal flats of the temperate Bahía Blanca estuary in the Atlantic coast of Buenos Aires province, Argentina. Several microbially induced sedimentary structures (MISS) occur especially in the upper intertidal and lower supratidal flats, among which the most conspicuous are erosional pockets, gas domes, microbial mat chips, and polygonal oscillation cracks. Biostabilization processes by epibenthic and endobenthic mats are also analyzed. Endobenthic mats occur in the upper intertidal area stabilizing ripples that despite the occurrence of severe storms persist in a fixed position for at least 2 months. Epibenthic mats occurring in the lower supratidal area also protect the substrate forming a thick microbial cover through the studied period. This thick cover was only affected by a strong storm that formed areas with erosional pockets and mat pieces. Nevertheless, the loose sediment within the erosional pockets was quickly colonized by microorganisms that developed a thin biofilm layer after a week. Changes in sediment accumulation were also recorded all over the upper tidal flat during a year, showing an important increase due to bioturbation activities of crabs. This situation also affected microbial mat growth, which evolved from a thin microbial biofilm into a thick, stratified microbial mat community in almost 2 years, mainly in the lower supratidal areas. The results of this study not only help us to better characterize the complex interactions between the microorganisms forming microbial mats, the tidal-flat sediment and the physical parameters that control this setting, but also have important implications for the understanding of analogous fossil sedimentary successions.